INTERACTIVE DISTANCE EDUCATIONAL TECHNOLOGIES IN GEOGRAPHY LESSONS - Viktor V. Hrushka (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология)
The formation of students’ geographical competence against the background of clarification and deepening of general geographical knowledge, skills and abilities, the formation of their own system of scientific judgments and values occurs during the study of geography. Students study a variety of geographical phenomena, processes, and patterns allowing understanding their dynamics and creating conditions for critical and sound analysis and comparison. Distance learning technologies include an individualized process of transfer and acquisition of knowledge, skills, abilities and methods for cognitive activity of students. Such techniques can be seen as a natural stage in the evolution of the traditional education system from chalk board to electronic board and computer technology. They provide the opportunity to conduct distance learning via the Internet; diversify the means of communication between student and teacher (e-mail, chat, forum, file sharing, etc.); activate the role of the teacher and exercise full control over the learning process; apply a multilevel testing system; Distance learning opens access to better; higher quality education for all participants in the learning process, but learning with the help of the Internet technologies is not sufficiently researched. This especially applies to the methodological development of educational support for e-learning courses, the operation of platforms for distance learning, the availability of professional staff, command of information technology for all participants in the educational process and more. The study compares the results of the formation of geographical knowledge in students in the control and experimental groups. The pedagogical conditions are substantiated and the main structural components of the organization of the process of formation of geographical knowledge in the institution of general secondary education are determined. Criteria and levels of formation of geographical knowledge of students in the learning process are determined. The effectiveness of the proposed teaching method in the implementation of distance education technologies using modern interactive platforms has been experimentally tested. The level of formation of cognitive interest of students in the process of studying the school course of geography in the 10th grade is determined. The analysis of results of control testing of pupils is made